"Gone to work to America": Irish step-migration through south Wales in the 1860s and 1870s. Issue 3 (1st September 2016) - Morris, David
Abstract: Why did the Irish-born population of Wales decline so sharply in the decade 1861–1870? This paper argues that during the 1850s and 1860s, large numbers of Irish men and women travelled to south Wales in order to finance emigration to the USA. Using the US Federal Census, this paper shows how Irish step-migration through Wales led principally to the Pennsylvania coalfields. This type of migration is termed the Knight's-move: a sideways move from agriculture into heavy industry, in order to advance forward across the Atlantic. The Knight's-move challenges previous assumptions about immigration into the south Wales coalfield during the nineteenth century.